Multi-functional adaptor SKAP1: regulator of integrin activation, the stop-signal, and the proliferation of T cells - Liu, Chen; Raab, Monika; Gui, Yirui; Rudd, Christopher E. (Frontiers in Immunology, 2023)
T-cell activation is a complex process involving a network of kinases and downstream molecular scaffolds or adaptors that integrate surface signals with effector functions. One key immune-specific adaptor is Src kinase-associated phosphoprotein 1 (SKAP1) which is also known as src kinase-associated protein of 55 kDa (SKAP55). This Mini-review explains how SKAP1 plays multiple roles in regulating integrin activation, the 'stop-signal' and, the optimization of the cell cycling of proliferating T-cells through interactions with various mediators, including the Polo-like kinase 1 (PLK1). Ongoing research on SKAP1 and its binding partners will likely provide important insights into the regulation of immune function and have implications for the development of new treatments for disease states such as cancer and autoimmunity.